Petrology and crustal inheritance of the Cloudy Bay Volcanics as derived from a fluvial conglomerate, Papuan Peninsula (Papua New Guinea): An example of geological inquiry in the absence of in situ outcrop. Issue 1 (1st January 2018) - Holm, Robert J.; Poke, Benny
Abstract: In regions of enhanced weathering and erosion, such as Papua New Guinea, our ability to examine a complete geological record can become compromised by the absence of in situ outcrops. In this study, we provide an example of the insights that can be gained from investigations of secondary deposits. We sampled matrix material and clasts derived from an isolated conglomerate outcrop within a landscape dominated by lowland tropical forest of the southeast Papuan Peninsula, and mapped as belonging to the Cloudy Bay Volcanics. Nine variations of volcanic rock types were identified that range from basalts to trachyandesites. Major and trace element geochemistry characterize the volcanic arc assemblage as shoshonites and provide evidence for differential magma evolution pathways with a subset of samples marked by heavy REE- and Y-depletion, indicative of high-pressure magma fractionation. Zircon U–Pb dating of the individual volcanic clasts indicates activity of the Cloudy Bay Volcanics was largely constrained to the latest Miocene, between ca. 7 and 5 Ma. Of the analyzed zircons, the majority are xenocrystic zircons that provide insight into the provenance of the Papuan Peninsula with potentially significant implications for South West Pacific tectonics. Additional Hf-isotope analysis of the primary igneous zircons suggests a relatively unradiogenic crustal component contributed to magma compositions, which cannot be readily explained by current regional tectonic paradigms.